2016
DOI: 10.1080/20786190.2016.1177977
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with medical consultations among adults attending Mulago hospital assessment centre

Abstract: Background Patient satisfaction is known to positively influence patients’ compliance with medical advice. In Africa, and specifically Uganda, this interaction has rarely been put to scientific inquiry. This study aimed to determine the level of patient satisfaction and identify factors influencing satisfaction with medical consultations among adults attending Mulago Assessment Centre. Methods This was a quantitative descriptive cross-sectional study where 384 respondents were interviewed using a structured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
3
11
1
Order By: Relevance
“…These findings indicate lower levels of patients satisfaction compared with those reported by some other studies. [ 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings indicate lower levels of patients satisfaction compared with those reported by some other studies. [ 11 12 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…Kabatooro et al . [ 11 ] reported that 53.9% of patients attending the Mulago Assessment Centre at a teaching hospital in Kampala, Uganda were satisfied with their received medical consultations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with the findings of a study carried out at Calabar Teaching Hospital in Nigeria (57.1%), Jimma (57.7%,), Debrebirhan hospital (61.9%), Amhara Region Referral Hospitals (65.9%) [11][12][13][14]. Allover patient satisfaction level was lower compared to the reports of the studies conducted in Jimma University Specialized Hospital (77%) and Hawassa University Teaching Hospital (80.1%), India (78%), Egypt (86.2%), Kenya (84%) [5,6,[15][16][17]. The difference might be due to the fact that those studies were conducted in specialized teaching and referral hospitals which are equipped very well and have enough diversity of health professionals, better diagnostic facilities, health service infrastructures, and awareness of service providers of different levels that are expected to demonstrate the standard way of patient examination resulting in higher level satisfaction.…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…To achieve high quality, the World Health Organization (WHO) now proposes a "people-centered" approach to health care, in which the patient is treated as a whole person with multiple needs, rather than just a disease condition to be managed. Patients' satisfaction with the services they receive is one way to quantify health-care quality [6]. The modern patient is more informed and educated, has greater access to information, and has higher expectations of the health-care system.…”
Section: Introductionmentioning
confidence: 99%